Replacement Value of Soybean Meal with Rapeseed Meal Supplemented with or Without a Dietary NSP-Dgrading Enzyme on Performance, Carcass Traits and Thyroid Hormones of Broiler Chickens - Kermanshahi, H.; Pour, A.R. Abbasi (International Journal of Poultry Science, 2006)
In a completely randomized design with 3*3 factorial arrangements and 4 replicates, 432 day-old Cobb male broiler chickens were used to evaluate the replacement of soybean meal with local grown rapeseed meal in the diet of broiler chickens with or without a dietary NSP degrading enzyme. The rapeseed meal was replaced with soybean meal at the levels of 0 (control), 15 and 30 percent for 6 weeks. The enzyme levels added to the diets were 0 (control), 0.025% and 0.050%. Feed intake, body weight gain and feed conversion ratio were adversely affected by added levels of rapeseed meal during the starter (0-21 d), grower (21-42 d) and overall feeding periods (P< 0.0001). Adding 0.025% enzyme significantly (0.004) improved body weight gain at starter period. The interactions between rapeseed and enzyme for body weight gain were significant in all periods (P< 0.001). Feed conversion ratio was not significantly affected by adding enzyme into the diets. Added levels of rapeseed meal significantly increased the weights of liver, proventriculus, gizzard (P< 0.0001) and abdominal fat pad (P< 0.028). Adding levels of rapeseed meal were also significantly increased the concentration of serum triiodothyronine (T3) at 42 days of age (P< 0.002) while adding enzyme into the diets had no significant effect among treatments . Therefore under the conditions of this study, use of lower levels of rapeseed meal might be more practical in broiler diets. For higher levels of replacement, further investigations are required.